2023
DOI: 10.1002/chem.202302740
|View full text |Cite
|
Sign up to set email alerts
|

o‐Hydroxyarylphosphanes: Strategies for Syntheses of Configurationally Stable, Electronically and Sterically Tunable Ambiphiles with Multiple Applications

Joachim W. Heinicke

Abstract: o‐Hydroxyarylphosphanes are fascinating compounds by their multiple‐reactivity features, attributed to the ambident hard and soft Lewis‐ and also Brønstedt acid‐base properties, wide tuning opportunities via backbone substituents with ±mesomeric and inductive, at P and in o‐position to P and O also steric effects, and in addition, the configurational stability at three‐valent phosphorus. Air sensitivity may be overcome by reversible protection with BH3, but the easy oxidation to P(V)‐compounds may also be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 319 publications
0
1
0
Order By: Relevance
“…3 Here we would like to report our contribution to a better understanding of the reaction of epoxides with phosphines. We have chosen a (diphenylphosphino)phenol derivative combining the phenol and the phosphine into a single molecule [20] to study in particular the first step of the reaction and found evidence for the elusive formation of phosphonium phenolate species reminiscent of II. The resulting zwitterionic molecules do not undergo the deoxygenation reaction and are thermally quite stable, making them potentially interesting as catalysts for various reactions such as the synthesis of cyclic carbonates from epoxides and CO 2 [21,22] or organophotoredox catalysis [23,24].…”
Section: Scheme 1 the Reaction Of Phosphines With Epoxides Resulting ...mentioning
confidence: 99%
“…3 Here we would like to report our contribution to a better understanding of the reaction of epoxides with phosphines. We have chosen a (diphenylphosphino)phenol derivative combining the phenol and the phosphine into a single molecule [20] to study in particular the first step of the reaction and found evidence for the elusive formation of phosphonium phenolate species reminiscent of II. The resulting zwitterionic molecules do not undergo the deoxygenation reaction and are thermally quite stable, making them potentially interesting as catalysts for various reactions such as the synthesis of cyclic carbonates from epoxides and CO 2 [21,22] or organophotoredox catalysis [23,24].…”
Section: Scheme 1 the Reaction Of Phosphines With Epoxides Resulting ...mentioning
confidence: 99%